The effects of the modern technologies on translating the media term from English language to Arabic: An analytical study - Al-Qaisy, Salah Sahi Khalaf (ALBAHITH ALALAMI, 2022)
The research aimed to identify the effects of the modern of technology on translating the media term from English language to Arabic. and try to identify the use of the impact of foreign media terminologies on the Arabic media term, and to know the effect of the translation process on Arabic media terminologies. This research is considered an analytical study by using survey study for 111 items and the results for the study as following: 1.High percentage of the (use of foreign terms work to low the level of production) was (68.13%) and average 3.55 2.The percentage of (The multiplicity of translation of the foreign term into Arabic effects on the opinions and cognitive ideas of the Arab researcher and affects the original language of the Arab citizen) was (72.3%) and average 3.92 3.The percentage of the (The lack of knowledge of the translator in the cultural and social field of the two languages created a weakness situation in filling the gaps in the Arab media term and the lack of knowledge of the translator rules of the science of terminology and its methods influenced on the Arabic media term) was (71.4%) and average 3.54 4.The percentage of the (The need to establish institutions that work on defining terms such as linguistic and scientific groups, translation and Arabization committees and effective Arab coordination in field of terms translation) was (72.6%) and average 3.58% .